The organisational commitment of workers in OECD countries - Andrew E. Clark (Management Revue, 2011)
The degree to which workers identify with their firms, and how hard they are willing to work for them, would seem to be key variables for the understanding of both firm productivity and individual labour-market outcomes. This paper uses repeated crosssection ISSP data from 1997 and 2005 to consider three of measures of worker commitment. There are enormous cross-country differences in these commitment measures, which are difficult to explain using individual- or job-related characteristics. These patterns do, however, correlate with some country-level variables. While unemployment and inflation are both associated with lower commitment to an extent, economic and civil liberties are positively correlated with worker effort and pride in the firm.
Keywords: J21; J28; J3; J6; J81; L26; 650; commitment; reciprocity; well-being